Relationship between nitrate, heavy metal, and sterols contents in Japanese agricultural soils with risk of groundwater pollution - Nakagawa, Kei; Islam, M. Shahidul; Shah, Syed Shabbar Hussain; Li, Zhuolin; Takao, Yuji; Berndtsson, Ronny (Chemosphere (Oxford), 2024)
In Japanese agricultural lands, nitrate-nitrogen contamination of soil and groundwater often occurs due to the application of livestock excrements and compost. Therefore, rural soils in Japan were sampled and analyzed for nitrate-nitrogen leaching, heavy metal content, and sterols associated with livestock excrement and compost to calculate contamination risk indicators. The results were analyzed using self-organizing maps and cluster analysis. Nitrate-nitrogen content using water extraction was detected in most of the sampled soils. In addition, many samples from areas that were already severely contaminated with nitrate-nitrogen showed particularly high concentrations. Coprostanol, an indicator of fecal contamination, was detected in more than half of the samples. The main source of nitrate-nitrogen contamination in these areas is livestock excrement and compost. Self-organization maps showed that areas with high nitrate-nitrogen contamination also corresponded to areas with high copper and zinc soil contents. The self-organization maps and cluster analysis resulted in five clusters: a nitrate-contaminated group mainly originating from livestock excrement and compost, a heavy metal-contaminated group, a general group, a nitrate-contaminated group mainly originating from chemical fertilizers, and a contaminated group with potentially hazardous substances requiring attention. Authorities and decision-makers can use the results to prioritize areas requiring remediation. [Display omitted] •Sources, distribution, and transformation of nitrate, heavy metals, and fecal pollution indicators in soil were analyzed.•High concentrations of nitrate in surface soil provided evidence of nitrate pollution in the adjoining water resources.•Sterol profiles indicated that 34% of the collected soil samples were associated with anthropogenic input of fecal origin.•Cu and Zn topsoil contamination coincided with nitrate-nitrogen contamination in groundwater.